PENGARUH PENDEKATAN PEMBELAJARAN SAINTIFIK TERHADAP KARAKTER SISWA KELAS VIII MTS NURUL HAKIM - Hizmi Wardani (Universitas Asahan, 2020)
Research is aimed to know the influence of the scientific learning approach to the character unification of students character. This research was conducted at MTs Nurul Hakim. This type of associative research, the dependent variable is the character of students, the independent variable is the scientific learning approach. The research instrument was a student character questionnaire and a scientific learning approach questionnaire. Data analysis technique is descriptive analysis, simple regression analysis. The results obtained by description of the average score is 26.35 with a standard deviation of 1.3485. Hypothesis testing results obtained Fcount ≥ Ftable or 6.975> 3.59 means that there is an influence of the scientific learning approach to the formation of student characters, while the results of the regression analysis are each additional 1% level of the scientific approach (X) then the character of students (Y1) will increase by 0.303 with the consistent value of student characters is 19.796 so the regression equation is Y = 19.796 + 0.303 X